SIMULATION MODEL OF SEDIMENT DYNAMICS IN AMUDARYA RIVER WATER - Murodov, Navruz (Innovatsion texnologiyalar, 2023)
The article presents the results of a study of the dynamics of suspended and bottom liquids in a water flow in relation to a deforming body. A simulation model that displays the hydraulic characteristics of turbid sediment particles makes it possible to control the turbidity regime in the channel and ensure the efficient operation of dredgers